EVALUASI PROSEDUR PENGELUARAN DANA PADA AKADEMI MARITIM NUSANTARA CILACAP - Indriyani; Altril Rayendra; Kristian Cahyandi (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2018)
This study aims to find out about the procedure of expenditure of funds at the Akademi Maritim Nusantara and know about the effectiveness of the implementation of procedures for expenditure of funds in accordance with Procedure no. PRO- AMN- OP037.bau. The data used in this research is secondary data obtained from Akademi Maritim Nusantara. The analytical method used descriptive method. It was concluded that the implementation of the fund disbursement procedure has been done well and in accordance with PRO-AMN-OP037.bau.